2020
DOI: 10.3390/ijerph17228463
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Multi-Agent Carbon Emission Reduction Strategy under the Chinese Dual Governance System: An Evolutionary Game Theoretical Approach

Abstract: A central-local dual governance system is the basic system of environmental governance in China. Co-governance between the central environmental protection department (CEPD) and local environmental protection departments (LEPDs) is an important means to effectively promote China’s carbon emission reduction strategy. Accordingly, this paper discusses their interactive decision-making and investigates how to optimize the strategic relationships between the CEPD, LEPDs, and carbon emission enterprises (CEEs) unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Wang et al [26] studied the regulation strategy of carbon emissions under the dual governance system of China by constructing an evolutionary game model between the central government, local government, and emission enterprises. In area of third-party regulation, Pan et al [27] found that when the government adopts positive regulatory strategy, the collusive behavior of enterprises and third-party supervision institutions can be reduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wang et al [26] studied the regulation strategy of carbon emissions under the dual governance system of China by constructing an evolutionary game model between the central government, local government, and emission enterprises. In area of third-party regulation, Pan et al [27] found that when the government adopts positive regulatory strategy, the collusive behavior of enterprises and third-party supervision institutions can be reduced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…eory in Social Governance. Many studies take government and enterprises as the main body and construct incentive regulation models based on evolutionary game theory [38,39]. Rocha et al used evolutionary game and input-output analysis methods to evaluate the strategic location choices of enterprises [40].…”
Section: Application Of Gamementioning
confidence: 99%
“…In addition to individual forms, the marine environmental protection social organizations (such as non-governmental environmental protection organizations and marine environmental protection associations) that exist in collective forms are also important social participants, and they are more active in terms of expressing their wishes for marine environmental governance, participating in governance policy formulation and development, supervising environmental governance and so on [ 25 ]. After years of development, several professional marine environmental protection social organizations have formed, such as the China Oceanographic Society, the “Blue Ribbon” Marine Conservation Association, and the Shenzhen Blue Marine Environmental Protection Association, but due to their late start, they still face various problems, such as incomplete management systems, imperfect legal systems, weak public foundations, single sources of funds and low professional levels [ 26 , 27 ].…”
Section: Subject Identification Of Modern Marine Environmental Governance In Chinamentioning
confidence: 99%